Building a New Model of Care for Rapid Breast Radiotherapy Treatment Planning: Evaluation of the Advanced Practice Radiation Therapist in Cavity Delineation. Issue 12 (December 2016) - Lee, G.; Dinniwell, R.; Liu, F.F.; Fyles, A.; Han, K.; Conrad, T.; Levin, W.; Marshall, A.; Purdie, T.G.; Koch, C.A.
Abstract: Aims: Breast radiotherapy treatment is commonly managed by a multidisciplinary team to ensure optimal delivery of care. We sought a new model of care whereby a clinical specialist radiation therapist (CSRT) delineates the cavity target for whole breast radiotherapy treatment planning and the radiation oncologist validates the contour during final plan review. This study evaluated the radiation oncologist's acceptance of these contours and identified characteristics of cavities suitable for CSRT-directed contouring. Materials and methods: Following specialised breast oncology education and training by the radiation oncologist, the CSRT prospectively delineated cavities in 30 tangential breast radiotherapy cases and consulted the radiation oncologist in 'complex' cases but directed 'non-complex' cases for treatment planning. Changes to CSRT contours were evaluated using the conformity index. Breast density, time since surgery and cavity location, size and visualisation score [CVS: range 1 (no visible cavity) to 5 (homogenous cavity)] were captured. Results: Of the 30 CSRT delineated cavities contours, the CSRT directed 20 (66.7%) cases for planning without radiation oncology review; 19 were accepted (without changes) by the radiation oncologist upon final plan review and one was changed by the radiation oncologist (conformity index = 0.93) for boost treatment and did not affect the tangential treatment plan. Ten (33.3%) cases, all CVS ≤ 3, were reviewed with the radiation oncologist before planning (conformity index = 0.88 ± 0.12). CVS was inversely correlated with breast density and cavity size ( P < 0.01). Conclusions: The CSRT delineated cavities appropriate for clinical radiotherapy treatment planning in women with well-visualised cavities, whereas 'complex' cases with dense breast parenchyma, CVS ≤ 3, and/or cases needing boost radiotherapy treatment required review with the radiation oncologist before planning. Highlights: Examination of a new model-of-care in breast radiotherapy treatment planning. Breast cavity contouring education and training provided by radiation oncologists. Prospective contouring of 30 cavities by the advanced practice radiation therapist. Physician acceptance of cavity contours was high for well-visualised cavities. Low visibility cavity and complex delineation cases require review with physicians.